2016
DOI: 10.1007/s12032-016-0790-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine by patients with cancer: a cross-sectional study at different points of cancer care

Abstract: Complementary and alternative medicine (CAM) is widely used by cancer patients. In order to learn more on the usage of CAM, its reasons and motifs as well as sources of information along the trajectory of treatment, we decided to evaluate the prevalence and predictors for the use of CAM by cancer patients while being under active treatment with chemo- or radiotherapy or in aftercare. We distributed a standardized questionnaire among patients attending a department of radio-oncology, an ambulance for oncology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 21 publications
7
49
3
1
Order By: Relevance
“…To integrate complementary medicine into evidence-based medicine, clinicians should be trained on how to communicate on complementary and alternative therapy CAT with the patient and with each other (Wortmann et al, 2016). Lack of knowledge within CAT undermines the ability of professionals to communicate the risks and benefits of CAT (Chang & Chang, 2015).…”
Section: Complementary and Alternative Therapymentioning
confidence: 99%
“…To integrate complementary medicine into evidence-based medicine, clinicians should be trained on how to communicate on complementary and alternative therapy CAT with the patient and with each other (Wortmann et al, 2016). Lack of knowledge within CAT undermines the ability of professionals to communicate the risks and benefits of CAT (Chang & Chang, 2015).…”
Section: Complementary and Alternative Therapymentioning
confidence: 99%
“…A meta-analysis published in 2012 estimated that 40% of cancer survivors worldwide use CTs, though estimates are slightly higher in North American countries (46%) and slightly lower in European countries (34%). 3 Several recent studies published since then have found similarly high rates of CT use 4 - 8 or higher. 1 , 9 - 12 Cancer survivors have reported several reasons for CT use, including alleviating side effects of treatment, improving health/healing/immune function, wanting control, and improving emotional/psychological functioning.…”
Section: Introductionmentioning
confidence: 96%
“…The rate of patients using complementary alternative medicine (CAM) in addition to the therapy regime or to alleviate side effects of cancer treatment ranges from 40 to 90% (Molassiotis et al 2005;Micke et al 2009;Huebner et al 2014;Wortmann et al 2016). However, only around 50% of these patients inform their general practitioner and 35%, their treating oncologist about using CAM.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, patients commonly use CAM additionally to standard treatment and herbals play a major role (Molassiotis et al 2005;Wortmann et al 2016). Several plants like Matricaria recutita L., Althaea officinalis L., Malva sylvestris L. or Calendula officinalis are known to TEM for treating oral mucositis (Büntzel et al 2019).…”
Section: Introductionmentioning
confidence: 99%